Substaging Nodal Status in Ampullary Carcinomas has Significant Prognostic Value: Proposed Revised Staging Based on an Analysis of 313 Well-Characterized Cases - Balci, Serdar (Ann Surg Oncol, 2015)
BACKGROUND: Current nodal staging (N-staging) of am-pullary carcinoma in the TNM staging system distinguishes between node-negative (N0) and node-positive (N1) disease but does not consider the metastatic lymph node (LN) number. METHODS: Overall, 313 patients who underwent pancreatoduodenectomy for ampullary adenocarcinoma were categorized as N0, N1 (1–2 metastatic LNs), or N2 (≥3 metastatic LNs), as proposed by Kang et al. Clinico-pathological features and overall survival (OS) of the three groups were compared. RESULTS: The median number of LNs examined was 11, and LN metastasis was present in 142 cases (45 %). When LN-positive cases were re-classified according to the proposed staging system, 82 were N1 (26 %) and 60 were N2 (19 %). There was a significant correlation between proposed N-stage and lymphovascular invasion, perineural invasion, increased tumor size (each p < 0.001), and surgical margin positivity (p = 0.001). The median OS in LN-negative cases was significantly longer than that in LN-positive cases (107.5 vs. 32 months; p < 0.001). Patients with N1 and N2 disease had median survivals of 40 and 24.5 months, respectively (p < 0.0001). In addition, 1-, 3-, and 5-year survivals were 88, 76, 62 %, respectively, for N0; 90, 55, 31.5 %, respectively, for N1; and 68, 34, 30 %, respectively for N2 (p < 0.001). Even with multivariate modeling, the association between higher proposed N stage and shorter survival persisted (hazard ratio 1.6 for N1 and 1.9 for N2; p = 0.018). CONCLUSIONS: Classification of nodal status in ampullary carcinomas based on the number of metastatic LNs has a significant prognostic value. A revised N-staging classification system should be incorporated into the TNM staging of ampullary cancers.